Pengembangan Bahan Ajar Kimia Berbasis Proyek dengan Multimedia Pada Materi Alkena di Sekolah Menengah Atas - Jamalum Purba; Rolian Ade Fitri (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2021)
This study aims to obtain: project-based teaching materials with multimedia that have met the criteria for content, language, presentation, and graphic eligibility according to the National Education Standards Agency and student responses to aspects of the appearance, material, and benefits of project-based teaching materials on Alkena material. The type of research used is Research and Development (R&D) which has been modified as needed. This research was carried out in several stages, namely syllabus analysis according to the current curriculum, book and multimedia analysis by researchers, design and development of teaching materials and multimedia, validation of teaching materials by lecturers and teachers, validation of multimedia by lecturers, and then the teaching materials developed were responded by students. The average result of the validation by lecturers and teachers is 3.67 which means valid. The average result of multimedia validation is 3.77 which means valid. The average percentage level of student satisfaction with project-based teaching materials with multimedia that has been developed is 90.33%. So it can be concluded that project-based teaching materials with multimedia on alkenes are valid and do not need to be revised. Based on the high student response, it means that students like the multimedia teaching materials.